The SmartAG partner: CCAFS East Africa Bi-annual Newsletter, July - December 2017 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
We are pleased to share with you our SmartAg Partner bi-annual newsletter, highlighting policy engagement and ongoing research from July to December 2017.